Exploring the Relationship between Metalinguistic Knowledge and Communicative Competence of Chilean EFL Teacher Trainees - Donoso, Eladio (Rastros Rostros, 2021)
There is enough evidence that Metalinguistic Knowledge (MK) benefits second language (SL) and foreign language (FL) learners’ communicative skills and SL and FL teachers’ classroom performance, therefore it should be an important component in SL and FL teacher training. Very little is known, however, about Chilean English as Foreign Language (EFL) teacher trainees, who are, at the same time, language learners. The study reported here aimed to find out the correlation and regression of future Chilean EFL teachers’ MK and their Communicative Competence (CC). In order to measure their MK, two tests were used: the Metalinguistic Knowledge Test and the Grammaticality Judgement Test. In regard to their CC, the grades of the English CC Development Course were considered. The participants were 59 first year EFL teacher trainees of an EFL teacher training program of a Chilean university. General results show that there is a positive moderate correlation between MK and CC and that the GJT and the MKT explain 26,5 % of the CC Final Grade.